Factors affecting refrigerator-freezers energy consumption - Saidur, Rahman; Masjuki, Haji Hassan; Mahlia, T.M.I.; Nasrudin, A.R. (ASEAN Journal on Science and Technology for Development, 2002)
Two refrigerator-freezers, one with a top-mounted freezer and one with side-by-side doors, were tested in the laboratory to determine the sensitivity of their energy consumption to various operational factors. Room temperature, room humidity, door openings, and the setting of the anti-sweat heater switch were the factors examined. The results indicated that the room temperature and door openings had a significantly greater effect on energy consumption than the other two factors. More detailed tests were then performed under different room temperature and door-opening combinations. The relationship of door openings and the equivalent test room temperature was established. Finally, the effect on energy of different temperature settings was studied. Test results are presented and discussed.